Sulfite reductase (sir) gene in rice (oryza sativa): bioinformatics and expression analyses under salt and drought stresses - Kurt, Fırat; Filiz, Ertuğrul; Aydın, Adnan (SPRINGER, 2021)
Rice sulfite reductase (OsSiR) is important protein in reducing sulfite to sulfide. In this paper, it is aimed to shed light on OsSiR's probable structure, function, and expression using in silico methods and test its responses under drought and salt stresses. Moreover, it was also analyzed if OsSiR was structurally different from other SiR proteins. We estimated that OsSiR lacks ribbon-helix-helix DNA-binding motif allowing it to bind to DNA; therefore, it was probably localized in stroma as a non-nucleoid-type protein. Also, we found that OsSiR expression was regulated by JA in roots and by crosstalk of JA and ABA in shoots. RT-qPCR results showed that there was 20% increase in the expression of OsSiR at 3rd h of the salt treatment. However, OsSiR was downregulated when exposed to drought stress and salt stress for longer periods of time, respectively. OsSiR has a high post-translational potential because of its high phosphorylation sites. This may be originating from the most prevalent residue, Gly, facilitating its binding to phosphates in OsSiR. Our docking results showed that ligand binding residues of OsSiR (Arg159, Thr162, Gln167, and Pro501) were also active site residues of OsSiR. Both two domains of OsSiR interacted with sulfite and the number of the residues in 4Fe-4S domain (PF01077) was higher. The findings in this study are important in terms of structural and expressional studies of rice SiR (OsSiR) and can be used for SiR proteins in sorghum (Sorghum bicolor), maize (Zea mays), and foxtail millet (Setaria italica), which are closely related and highly similar to OsSiR in terms of sequence and predicted 3D structure.
Keywords: Sulphur; Oryza sativa; Sulfite reductase; Bioinformatics; Molecular docking